CHANGES IN THE TAXONOMY OF THE SPECIES OF THE ERIBIDAE FAMILY (LYMANTRIA DISPAR) AND THE RANGE OF PESTS (Scientific journal of the Fergana State University, 2024)
In the article, the bioecology of the Eribidae family (Limantria dispar), the level of harmfulness to the environment, and the data are presented. Not all species of the silkworm family are considered pests. (Limantria dispar) species poses a serious threat to plants and agriculture due to its high pest level. The obtained results allow finding practical and theoretical problems and solutions.